2023
DOI: 10.3390/foods12020328
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Glutopeak Test and Mixograph Parameters for Evaluation of Wheat Flour Supplemented with Hazelnut Skin, Cross-Linked Starch, and Oxidized Starch

Abstract: Hazelnut skin is a by-product produced from hazelnut processing. It can be used as a nutritional supplement due to its high nutrient values. The purpose of this study was to evaluate the dough properties of refined flour (RF) with the addition of hazelnut skin (HS), cross-linked starch (CS), and oxidized starch (OS). Principal component analysis showed a positive correlation between maximum torque, torque after maximum, and aggregation energy. Usage of 10% HS significantly (p < 0.05) decreased the mixograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The GlutoPeak test has here been used as a rapid method for assessing gluten quality (Durmus et al., 2023). Sissons (2016) already indicated that the peak mixing time of a GlutoPeak test can serve as a viable alternative for evaluating gluten strength, in lieu of the more time‐consuming mixograph and gluten index analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The GlutoPeak test has here been used as a rapid method for assessing gluten quality (Durmus et al., 2023). Sissons (2016) already indicated that the peak mixing time of a GlutoPeak test can serve as a viable alternative for evaluating gluten strength, in lieu of the more time‐consuming mixograph and gluten index analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Different additives are used to improve the mixing properties of dough, mostly for weak flour (Jazaeri et al, 2015; Lang et al, 1992; Nash et al, 2006). The mixograph is often used to determine the dough mixing properties (Durmus et al, 2023; Nkurikiye et al, 2023; Tebben et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…), can also be used in breadmaking to improve the nutritional value of bread due to its high dietary fiber and phenolic content. Many studies show that hazelnut skin is a rich and low‐cost source of natural phenolic antioxidants (Contini et al, 2008; Durmus, Anil, & Simsek, 2023; Shahidi et al, 2007). Some researchers produced bread with hazelnut skin and found that the crust and crumb darkness of bread increased and obtained similar or slightly low loaf volumes and sensory properties (Anil, 2007; Velioglu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%